Optimization of peripheral blood volume for in silico reconstitution of the human B‐cell receptor repertoire. Issue 9 (9th August 2022) - Lee, Hyunho; Yoo, Duck Kyun; Han, Jerome; Kim, Ki Hyun; Noh, Jinsung; Lee, Yonghee; Lee, Eunjae; Kwon, Sunghoon; Chung, Junho
Abstract : B cells recognize antigens via membrane‐expressed B‐cell receptors (BCR) and antibodies. Similar human BCR sequences are frequently found at a significantly higher frequency than that theoretically calculated. Patients infected with SARS‐CoV2 and HIV or with autoimmune diseases share very similar BCRs. Therefore, in silico reconstitution of BCR repertoires and identification of stereotypical BCR sequences related to human pathology have diagnostic potential. Furthermore, monitoring changes of clinically significant BCR sequences and isotype conversion has prognostic potential. For BCR repertoire analysis, peripheral blood (PB) is the most convenient source. However, the optimal human PB volume for in silico reconstitution of the BCR repertoire has not been studied in detail. Here, we sampled 5, 10, and 20 mL PB from the left arm and 40 mL PB from the right arm of two volunteers, reconstituted in silico PB BCR repertoires, and compared their composition. In both volunteers, PB sampling over 20 mL resulted in slight increases in functional unique sequences (FUSs) or almost no increase in repertoire diversity. All FUSs with a frequency above 0.08% or 0.03% in the 40 mL PB BCR repertoire were detected even in the 5 mL PB BCR repertoire from each volunteer. FUSs with a higher frequency were more likely to be found in BCR repertoires from reduced PB volume, and those coexisting in two repertoires showed a statistically significant correlation in frequency irrespective of sampled anatomical site. The correlation was more significant in higher‐frequency FUSs. These observations support the potential of BCR repertoire analysis for diagnosis. Abstract : Peripheral blood (PB) is the most convenient source for BCR repertoire analysis. However, the optimal volume for in silico analysis of the BCR repertoire has not been studied in detail. We sampled various volumes of human PB from different anatomical sites to compare the functional unique sequences that coexist among the repertoires in order to suggest optimal PB volume.